Investigation of High-temperature Oxidation Kinetics and Residual Ductility of Oxidized Samples of Sponge-based E110 Alloy Cladding Tubes. (20th December 2016) - Yan, Y.; Garrison, B. E.; Smith, T. S.; Howell, M.; Keiser, J. R.; Bell, G. L.
ABSTRACT: Two-sided oxidation experiments were recently conducted at 1000-1200°C in flowing steam with samples of sponge-based Zr-1Nb alloy E110. Although the old electrolytic E110 tubing exhibited a high degree of susceptibility to nodular corrosion and experienced breakaway oxidation rates in relatively short time, the new sponge-based E110 has demonstrated steam oxidation behavior comparable to Zircaloy-4. The sponge-based E110 followed the parabolic law, and the derived oxidation rate constant is in good agreement with the Cathcart-Pawel (CP) correlation at 1100-1200°C. For 1000°C oxidation, the weight-gain of sponge-based E110 is much lower than Zircaloy-4. No breakaway oxidation was observed at 1000°C up to 8000 s. Ring compression tests were conducted to evaluate the residual ductility of oxidized samples at room temperature and at 135°C. All sponge-based E110 specimens were still ductile at 135°C after being oxidized up to 20% equivalent cladding reacted at 1000-1200°C. Metallographic examinations were performed on oxidized E110 specimens to correlate material performance with microstructure.